2013
DOI: 10.1111/bjh.12627
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antiphospholipid antibodies in psychiatric patients users and non‐users of antipsychotics

Abstract: SummaryPast reports have suggested that antiphospholipid (aPL) antibodies may emerge as a response to antipsychotics treatment, as a high prevalence of aPL antibodies in antipsychotics users has been observed. However, no control group of non-medicated psychiatric patients was included in these reports. In a cross sectional study we determined the prevalence of aPL antibodies in 333 psychiatric inpatients. We compared the proportions of positive aPL antibodytests between users and non-users of antipsychotics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
(41 reference statements)
0
10
0
Order By: Relevance
“… 61 Conditions characterized by low protein S activity, such as systemic lupus erythematosus, Behçet's disease and Sjögren's syndrome may present with cognitive impairment, delusions and hallucinations. 9 , 62 In addition, puerperal psychosis occurs when protein S levels are low, regardless of systemic inflammation. 63 …”
Section: Links Between Biochemical Abnormalities Of Schizophrenia Andmentioning
confidence: 99%
See 2 more Smart Citations
“… 61 Conditions characterized by low protein S activity, such as systemic lupus erythematosus, Behçet's disease and Sjögren's syndrome may present with cognitive impairment, delusions and hallucinations. 9 , 62 In addition, puerperal psychosis occurs when protein S levels are low, regardless of systemic inflammation. 63 …”
Section: Links Between Biochemical Abnormalities Of Schizophrenia Andmentioning
confidence: 99%
“…Antiphospholipid antibodies such as anticardiolipin antibodies and lupus anticoagulant are highly prevalent in drug-naive schizophrenia. 9 , 10 , 11 The diagnosis of antiphospholipid antibody syndrome requires the persistence of antibodies, plus either a thrombotic event or an obstetric complication due to abnormal placentation. 67 Patients with antiphospholipid antibodies may present with cognitive dysfunction or full-blown psychosis, independent of brain ischemia.…”
Section: Links Between Biochemical Abnormalities Of Schizophrenia Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Markers of low tPA activity consistently described in schizophrenia include hyperhomocysteinemia and antiphospholipid antibodies, such as lupus anticoagulant and IgM isotype anticardiolipin antibody [ 16 , 17 , 18 ]. Importantly, both hyperhomocysteinemia and antiphospholipid antibodies may affect tPA activity without affecting tPA levels [ 19 ].…”
Section: Conditions That Inhibit Tpa Function Are Prevalent In Schmentioning
confidence: 99%
“…Some reports have also suggested that APLA may emerge as a response to antipsychotic treatment, since a high prevalence of the antibodies in antipsychotic users has been observed. A recent cross-sectional study determined the presence and a subtype of APLA in 333 psychiatric inpatients: APLA were frequently found positive, and prevalence of the antibodies was not significantly different in patients who were receiving, or not receiving, antipsychotics 39. Long-term prospective epidemiological cohort studies are still needed to analyze possible pathogenic implications of persistent APLA in psychiatric patients, such as worsening of the clinical symptomatology.…”
Section: Association Of Thrombotic Risk Markers With Mental Disordersmentioning
confidence: 99%